The Right Tax (Tufts Archival Research Center, 2007)
Op-Ed from The Louisville, KY Courier-Journal. Discusses Clinton’s proposed excise tax increase and its impact on Kentucky. Argues that the tax is fair due to higher health costs for smokers and that the health of the nation is more important than the economy of Kentucky. Suggests that tax money could aid tobacco farmers to convert their fields for other crops.